An open platform for agent-based modeling of spatial economics: conceptual framework and practical application - Bobylev Georgiy (π-Economy)
The relevance of the study is due to the need to develop agent-based modeling (ABM), especially in the context of creating complex models covering several industries and regions. The key problems in this area include the low speed of model development and their insufficient connection with real-world processes. This work aims to address these problems related to the development of agent-based models (AB models) of spatial economics. Additionally, the study is aimed at systematizing the experience and knowledge of the author team in the field of ABM platforms. The goal of the research is to develop a conceptual framework for an open platform for agent-based modeling of spatial economics (OPABMSE). The work is comprehensive and is based on a systemic and structural approach and draws on, among others, the following areas of scientific literature: issues of development of digital and software platforms, application of ABM in decision support and decision-making systems, digital and spatial economics, application of agent-based multiregional input-output models for analyzing the Russian economy. The paper introduces a new definition of OPABMSE as an instrumental and infrastructural digital platform with an open architecture based on software for developing AB models. The platform is designed for joint work of a large community of researchers on large AB models of the Russian economy and the provision of ABM services. A conceptual framework for OPABMSE is proposed, which takes into account the external environment, information infrastructure, and users from industry, economic science and education, as well as government bodies. The main structural elements of the platform are described. The use of OPABMSE is very promising due to its potential in solving a wide range of scientific and applied problems. This platform can be used as part of a decision support and decision-making system in economy. OPABMSE will help government bodies and industry representatives analyze the possible consequences of making certain decisions. Economic science and education will be able to use OPABMSE to solve various problems in the field of spatial economics. This platform can become a useful tool for research work when writing graduate qualification papers in economic specialties. The proposed conceptual framework for OPABMSE has the potential for further practical implementation.